Allogenic Platelet-Rich Plasma for Treating Cartilage Injury: A Systematic Review of the Evidence on the Basic Sciences for Potential Future Applications - Hassan, Nur Hidayah; Ahmad, Raja Elina; Kamarul, Tunku; Looi, Qi Hao Daniel; Chong, Pan Pan (Cells, tissues, organs, 2024)
It is apparent that whilst many reports are available regarding platelet-rich-plasma (PRP), the larger majority of these have been mainly focussed on autologous sources, and for good reason. Issues relating to allogenic source have been consciously avoided owing to concerns of cross infectivity and immune rejection. However, this topic today is now revisited and is of interest since progress over the year has demonstrated its safety, efficacy, and its abundance of supply. The present systematic review was thus conducted to elucidate advances made in this area, with the aim to provide a wider and deeper understanding of studies relevant to the application of allogenic PRP in cartilage repair. Literature search was conducted systematically using Medline, ProQuest, Web of Science, Cochrane Central Register of Controlled Trials, and snowballing searching strategy to identify relevant studies using topic-specific keywords in various combinations including "allogenic, platelet, rich, plasma" OR "allogeneic, platelet, rich, plasma" OR "allogenic platelet-rich plasma" OR "allogeneic platelet-rich plasma" OR "allogenic platelet rich plasma" OR "allogeneic platelet rich plasma" AND cartilage OR chondrocytes OR synoviocytes OR stem cells. Studies that used allogenic PRP in an attempt to facilitate cartilage repair were included. The risk of bias was assessed by the SYRCLE's checklist. Of 206 studies identified, 12 were found eligible. Only those studies that are clearly related and specific to allogenic PRP were included. Of these, nine investigated the efficacy of allogenic PRP in animal models, while three articles employed an in vitro model. Allogenic PRP promotes cell proliferation, cartilage matrix production, and anti-inflammatory effects in vitro. The in vivo studies reported histological evidence of significant acceleration of cartilage repair in treated animals. Despite several conflicting findings, all studies agreed that allogenic PRP is safe and potentially efficacious for cartilage repair, with the advantages of allogenic sources apparent.